Bilateral Total Hip Arthroplasties Secondary to Renal Osteodystrophy in a Patient with a Rare Cromer Antibody: A Case Report - Anisha Tyagi; Caldon Jayson Esdaille; Ajith Kumar Kannan; Jennifer Joseph; James Lee Jr; Rahul Mittal (Journal of Orthopaedic Case Reports)
Introduction: Bilateral displaced femoral neck fractures are uncommon in adults without significant trauma, especially in the absence of high-energy impact. This case highlights the importance of considering underlying metabolic disorders such as end-stage renal disease (ESRD) as significant contributing factors. It is one of the few reported cases demonstrating the interplay between ESRD, renal osteodystrophy, anemia of chronic disease, and the presence of rare Cromer blood group antibodies, adding a unique dimension to orthopedic and hematological literature. Case Report: We present the case of a 50-year-old African American female with a history of ESRD on dialysis, who presented with bilateral hip pain after a minor fall. Imaging revealed bilateral displaced femoral neck fractures. Laboratory workup showed a hemoglobin level of 7.4 g/dL and microcytic anemia. Due to her chronic kidney disease, she was diagnosed with renal osteodystrophy, contributing to bone fragility. A rare Cromer blood group antibody was also detected, complicating transfusion planning. She underwent surgical repair of both hips, and her post-operative management involved coordinated multidisciplinary care addressing orthopedic, hematologic, and nephrologic concerns. Conclusion: This case underscores the need for clinicians to consider renal osteodystrophy in patients with ESRD as a potential cause of spontaneous or low-impact fractures. In addition, it highlights the transfusion challenges posed by rare blood group antibodies like those in the Cromer system. The case demonstrates the value of early recognition, prompt surgical intervention, and interprofessional collaboration in managing complex comorbid conditions. It contributes to broader clinical understanding by linking metabolic bone disease, chronic anemia, and immunohematologic complications in fracture management. Further research into personalized treatment protocols and rare blood antigen matching could enhance outcomes for such medically complex patients.